The access of adolescents deprived of liberty in the SUS network - Oliveira , Wallace Hugo Cangussu; Barreto, Sandra Silva Lima; Bragio, Jaqueline (Seven Editora, 2024)
This paper reports the experience in the health care of adolescents and young people deprived of liberty and the implementation of the National Policy for Comprehensive Health Care for Adolescents in Conflict with the Law, in Hospitalization, Provisional Hospitalization and Semi-Freedom (PNAISARI) in the State of Espírito Santo. This Policy aims to help ensure access to health services in the Unified Health System (SUS) network for this public, promoting promotion and prevention actions, in addition to their social reintegration. This is a descriptive and qualitative study, based on an experience report in working with socio-educational measures in a closed environment. Its objective is to describe actions of articulation and management of the health demands of socio-learners of the executing agency of the socio-education policy in a closed environment in the State. The present work also discusses the aspect of human rights in articulation with the right to health, recognizing the importance of intersectoriality in the management of the comprehensive health care policy for adolescents and young people in compliance with socio-educational measures, as well as the co-responsibility of the various actors and services of the care network, in order to guarantee the fundamental right to health. It was observed that there is still a punitive perspective and the stigma of dangerousness directed at the public in question that act as barriers to their access to health, so that using an educational approach in human rights can be a good strategy to minimize these obstacles. DOI:https://doi.org/10.56238/sevened2024.001-028